Familial germ cell tumor - Cyriac, Sanju (Medknow Publications & Media Pvt Ltd, 2012)
Familial testicular germ cell tumors are well known in literature. Only few cases are reported where both brother and sister of the same family suffered from germ cell malignancies. We present a family where the proband is a survivor of ovarian dysgerminoma stage IA. Her elder male sibling became acutely ill and was detected to have disseminated testicular malignancy with grossly elevated markers and vegetations in the mitral valve leaflets. Despite all measures he could not be saved. Presence of germ cell malignancies in the siblings of different sex in the same family points toward a genetic susceptibility. Literature review revealed only six similar cases. A discussion regarding the rare occurrence of familial germ cell malignancies with the affected family members may be worthwhile.